Chemical characteristics of aerosol and rain water during an El Niño and PDO influenced Indian summer monsoon. (November 2016) - Rajeev, Pradhi; Rajput, Prashant; Gupta, Tarun
Abstract: According to the meteorological long-term variability pattern, year 2015 was influenced by El Niño and PDO (Pacific Decadal Oscillation; causes weakening of Indian Summer Monsoon). These conditions facilitate the assessment of chemical characteristics of fine-mode ambient aerosols (PM2.5 ; n = 48) and individual rain waters (pH: 6.4–7.6; n = 15) during the South-west monsoon (July–September 2015) in the central Indo-Gangetic Plain (IGP; Kanpur). Water-soluble ionic species (WSIS) have been measured to assess the undergoing processes (neutralization, formation and below-cloud scavenging) and estimate their dry and wet deposition fluxes. The ∑WSIS varies from 4 to 32 μg/m 3 in PM2.5, whereas it ranges from 32 to 102 mg/L in rain waters. The NH4 + and SO4 2− are found to be predominant in PM2.5 (16–120 μg/m 3 ), whereas HCO3 − and Ca 2+ are predominant in rain water samples. The difference in chemical composition of PM2.5 and rain water is largely attributed to additional contribution of coarse-mode mineral dust in rain water. The Ca 2+ and Mg 2+ in both aerosols and rain water samples are associated with HCO3 − . The NO3 − and SO4 2− are neutralized predominantly by NH4 + and ∑ − /∑ + ratio is ≈ 1 in both aerosols and rain waters. Furthermore, co-variability of NO3 − with nss-Ca 2+ in PM2.5 indicates role of fine-mode mineral dust surface in the formation of ammonium nitrate. Characteristic mass ratios (HCO3 − /Ca 2+ and SO4 2− /NH4 + ) in rain water look quite similar to those in aerosols (PM2.5 ). This suggests that below-cloud scavenging is predominant mechanism of aerosols wash-out. Dry deposition fluxes of Mg 2+, NH4 + and SO4 2− are ∼13% of their wet deposition fluxes, whereas for K +, Ca 2+ and NO3 − it is <6%. Graphical abstract: Highlights: Chemical characteristics of aerosols and rain water in IGP during SW-monsoon. Predominant neutralization of acidic species by NH4 + (rain water pH: 6.4–7.6). NO3 − formation processes during SW-monsoon. Below-cloud scavenging is predominant wash-out mechanism. Dry and wet deposition fluxes have been estimated.